Competitiveness of the UK Fertility Market - A National Comparative Assessment - Ogunmokun, Adebola/H (2009)
The fertility Industry in the UK has continuously faced threats from international competition. This is evident in the growing rate at which fertility patient’s travel to other international markets for fertility treatments. A Europe-wide study suggests that ‘hundreds of British couples travel to the continent every month for fertility treatment because they cannot get it at home’ (BBC Website). The Czech market, in particular, has been a major market for patients travelling for fertility treatments with many more patronising the country because of the relatively cheaper cost of service as well as availability of donor eggs among other things. Adopting the Porters Comparative Diamond framework reveals that the factor conditions in the UK fertility Industry are relatively less competitive because the price offering, as well as governing regulatory practices, make services less accessible to patients relative to what obtains in the Czech market. Hence, though the situation may pose limiting factors for investment in UK fertility market, nevertheless the study seeks to review relative competitiveness of the Czech and UK fertility market for possible efficiency gains. The study utilises a standardisation framework to assess the degree of similarities that exists in both markets and hence proposes a point through which investments in both markets can be beneficial.